Lived experiences of patients using positive airway pressure (PAP) therapy: a nested phenomenological study within the 3DPiPPIn randomised controlled trial - Stephanie K Mansell; Cherry Kilbride; Swapna Mandal; Eleanor Main; Francesca Gowing; Silvia Schievano; Stephen T. Hilton (BMJ Open)
Background Sleep disordered breathing is a chronic condition often requiring patient commitment to positive airway pressure (PAP) therapy. Understanding the lived experience of PAP therapy users is crucial for clinicians to support successful treatment and identify research priorities. There is a lack of evidence in this area, and published data predominantly explore the negative experiences of PAP. This study aims to explore the lived experiences of patients using PAP therapy.Methods and analysis This study employs a phenomenological approach, appropriate for researching human experiences where there is little existing research. Heideggerian theory underpins the research, recognising that the researcher’s beliefs influence meaning, allowing for rich analysis of the lived experience.Participants will be recruited from a randomised controlled trial investigating the medium-term clinical impact of customised interfaces for patients requiring PAP therapy. Purposive sampling will be used to seek representation from various demographics, with a maximum of 30 participants.Data collection will be via 1:1 semistructured interviews. Data will be analysed using Braun and Clarke’s six-phase reflexive thematic analysis. Data will be analysed inductively through an interpretivism lens. Data will be managed with computer-assisted qualitative data analysis software.Ethics and dissemination This protocol has been approved by the Hampshire B Research Ethics Committee (REC reference: 22/SC/0405). Results will be disseminated to healthcare professionals and patients through conferences, open-access journals, newsletters, the study webpage, infographics, animations, social media and healthcare awards. Tracy’s eight ‘big tent’ criteria for excellent qualitative research are comprehensive and encompassing, and this protocol has aimed to meet the criteria. The Consolidated Criteria for Reporting Qualitative Research has also been used. The findings of this study will contribute to a more holistic understanding of the lived experience of PAP therapy users, informing clinical practice and future research.Trial registration number ISRCTN74082423.